Vocal Fold Motion Impairment Following Chemotherapy Administration: Case Reports and Review of the Literature. (April 2021) - Talmor, Guy; Nguyen, Brandon; Geller, Melin Tan; Hsu, Jeffrey; Kaye, Rachel; Caloway, Christen
Objective: Chemotherapy-induced vocal fold motion impairment (CIVFMI) is a rare complication of cancer therapy with potential for airway compromise. The objective of this review is to present 2 new cases of CIVFMI to add to the literature as well as characterize the demographics, symptoms, exam findings, airway complication rates and prognosis of CIVFMI. Methods: A search of Pubmed/MEDLINE (1970 to May 1, 2020), Embase (1970 to May 1, 2020), and Cochrane Library using medical study heading (MeSH) terms related to chemotherapy ( drug therapy, chemotherapy, vincristine, vinblastine, paclitaxel ) and vocal cord motion impairment ( vocal cord, cords, vocal folds, immobility, hypomobility ) was performed. Exploratory pooling of data without formal meta-analysis was performed. Results: A preliminary search yielded 148 abstracts, review articles and studies. A total of 23 studies met inclusion criteria. There were 35 total cases presented in the literature, with a mean age of 29.5 (0.4-78). The most common cancer diagnosis was acute lymphoblastic leukemia (n = 15, 42.9%), and the most common agent was vincristine (n = 30, 85.7%). Dysphagia, bilateral CIVFMI, and vocal fold immobility rather than hypomobility were more common in pediatric patients. There were 8 cases of surgical airway intervention, including tracheostomy and posterior cordotomy. The duration of symptoms was 7 to 420 days, and spontaneous resolution was reported in 32 cases. Conclusions: CIVFMI has potential for airway complications requiring surgical intervention. Spontaneous resolution after cessation of the offending agent is the most likely outcome. Bilateral CIVFMI, dysphagia and vocal fold immobility are more common in the pediatric population.